Soft Skills Intelligence In Generation Z For Enhancing Future Success - Sutoyo; Apri Winge Adindo (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The rapid development of the digital era and the emergence of the Industrial Revolution 5.0 require Generation Z to possess not only technological competence (hard skills) but also strong soft skills intelligence, including communication, collaboration, leadership, empathy, and adaptability. This study aims to analyze the role of soft skills intelligence in enhancing future success among Generation Z and to identify educational strategies for its development based on Islamic values. This research employed a qualitative library research design, utilizing secondary data sources such as peer-reviewed journal articles, academic books, policy documents, and classical as well as contemporary Islamic education literature. Data were analyzed through thematic content analysis focusing on the conceptual relationship between soft skills intelligence, emotional intelligence, and Islamic educational principles.The findings indicate that soft skills intelligence functions as a critical determinant of Generation Z’s future success, particularly in strengthening emotional regulation, ethical decision-making, leadership capacity, and adaptability in digital-social environments. Furthermore, the study reveals that the integration of Islamic values—such as akhlaq al-karimah, uswah hasanah, tazkiyatun nafs, and social responsibility—significantly enhances the effectiveness of soft skills development, distinguishing it from purely secular competency frameworks. This study contributes uniquely by offering an integrative conceptual model of soft skills intelligence grounded in Islamic educational values, providing a value-based framework for educators and policymakers to design holistic learning environments that respond to the socio-emotional challenges faced by Generation Z in the digital era.